Volume 9: Supercritical CO2 2022
DOI: 10.1115/gt2022-82013
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 2 MW Molten Salt Driven Supercritical CO2 Cycle and Turbomachinery for the SOLARSCO2OL Demonstration Project

Abstract: Supercritical CO2 (sCO2) power cycles have been identified as technology enablers for increasing the cost-competitiveness of Concentrating Solar Power (CSP) plants. Compared to steam cycles, sCO2 cycles have the advantage of allowing higher inlet turbine temperatures, while also deploying turbomachinery that can be a ten-fold more compact. Ongoing research in CSP focuses mainly in developing new receiver and storage concepts able to withstand such required higher temperatures, alongside new heat exchangers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The SOLARSCO2OL [11] Horizon2020 European project aims at the installation and demonstration of a first-of-a-kind MW-scale sCO2 plant coupled with CSP in Europe. The sCO2 demo plant will be installed at the premises of the University of Evora and coupled with a pre-existing CSP plant using molten salts (MS) as heat transfer fluid.…”
Section: The Demo-cycle and The Solarsco2ol Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOLARSCO2OL [11] Horizon2020 European project aims at the installation and demonstration of a first-of-a-kind MW-scale sCO2 plant coupled with CSP in Europe. The sCO2 demo plant will be installed at the premises of the University of Evora and coupled with a pre-existing CSP plant using molten salts (MS) as heat transfer fluid.…”
Section: The Demo-cycle and The Solarsco2ol Projectmentioning
confidence: 99%
“…This solution has a cycle efficiency of 21.3%. However, the study by Guedez et al [11] demonstrated that an upscaled version of this concept could reach an efficiency higher than 31%, and adding recompression to the plant could lead to almost 50%.…”
Section: The Demo-cycle and The Solarsco2ol Projectmentioning
confidence: 99%
“…sCO 2 could make this possible via WH P2H2P solutions exploiting sCO 2 HPs and power cycles. Based on previous thermo-economic analysis of advanced sCO 2 power cycles [35] and thermal energy storage for industries [36], in this paper an innovative layout and concept is proposed, aiming at valorizing industrial WH and achieving attractive round-trip efficiency (RTE).…”
Section: Industrial Sectors Assessment For Grid Flexibilitymentioning
confidence: 99%
“…In this case, the above presented PTES cycle was studied starting from an analysis of the discharging cycle with a maximum pressure limit of 250 bar and a TES with a temperature of 450 • C (HITEC XL as the TES media). This value was determined by the authors based on their previous study [35] considering technological factors to ensure manageable compression ratios and the use of pressurized HEXs among other considerations. Additionally, in accordance with the assumptions made, a maximum CO 2 temperature of 440 • C and a typical compressor inlet temperature of 35 • C were selected to ensure stable compressor operation.…”
Section: Operating Pressure Of Charging and Discharging Cyclesmentioning
confidence: 99%
See 1 more Smart Citation